Determinants of Selected Cardiovascular Diseases among Adult Patients at Cardiac Clinic of Debre Berhan Referral Hospital, Ethiopia: Unmatched Case-Control Study. (27th May 2020) - Aragaw, Shenkut; Tesfahun, Esubalew; Derseh, Behailu Tariku; Mamo, Betegiorgis
Abstract : Background . Africans are experiencing a rapid epidemiological transition characterized by urbanization and lifestyle changes, which are thought to contribute to increased incidence and prevalence of cardiovascular diseases (CVDs) in many African countries, including Ethiopia. Despite this, however, there is scarcity of evidence on cardiovascular disease risk factors among adults in the current research setting. This study thus aimed at assessing determinants of selected cardiovascular diseases among adult patients at Debre Berhan Referral Hospital (DBRH). Methodology . An unmatched case-control study was conducted on 143 newly diagnosed patients with CVDs and 286 controls at the cardiac clinic of DBRH from June to September 2017. Primary data were collected using the WHO-STEPS wise structured questionnaires. Multiple logistic regression analysis was used to identify potential risk factors for cardiovascular diseases at p values < 0.05. Result . The mean age of study participants is estimated as 45.5 ± 13.8 and ranges from 25 to 64 years. Sixty-one (42.7%) of cases and 147 (51.4%) of controls are males. Half of the cases (49.9%) had ischemic heart diseases (IHD), and 44.1% of cases had hypertensive heart disease (HHD), whereas the rest had chronic valvular heart disease (CRVHD) (4.2%) and peripheral and vascular disease (2.1%). This study identified older age as a risk factor for CVD: age group 35–44 years (adjusted   odds   ratio   AOR = 2.20 ; 95% CI: 1.05–4.62), 45-54 years (AOR = 4.23 ; 95% CI: 2.19–8.16), and 55-64 years (AOR = 5.98 ; 95% CI: 3.26–10.98). Other risk factors were smoking history (AOR = 9.52 ; 95% CI: 2.12–42.8), low level of physical activity (AOR = 2.19 ; 95% CI: 1.10–5.02), and higher waist circumference (AOR = 2.75 ; 95% CI: 1.16–6.56). Conclusion . This study has demonstrated that the most frequent risk factors for CVD were older age, cigarette smoking, physical inactivity, and abdominal obesity. Therefore, behavior change communication focusing on lifestyle modification including regular physical activities, smoking cessation, and a balanced diet should be strengthened.